KEWIRAUSAHAAN HIJAU: PROFESIONALITAS MANAJEMEN BANK SAMPAH UNTUK PENINGKATAN KESEJAHTERAAN MASYARAKAT - Kurniaty, Dewi; Subagio, Aris; Moersid, Rambo Anzhar; Mukminah, Salsa; Poetry, Keyka (Jurnal Abdimas Bina Bangsa, 2024)
Waste management in Jakarta is a major challenge, with increasing waste volumes. Mekarsari Waste Bank offers an innovative solution to address environmental issues while creating economic value through recycling. This community empowerment program focuses on enhancing management and digital marketing capabilities to optimize operations and increase community involvement. The method used in this service is Participatory Rural Appraisal (PRA), involving the community at every stage. The results demonstrate improved financial management effectiveness, increased customers, and expanded marketing reach through social media. This activity proves that integrated and sustainable waste management not only contributes to environmental sustainability but also enhances community welfare